Anastomotic reinforcement with omentoplasty following gastrointestinal anastomosis: A systematic review and meta-analysis. (September 2015) - Wiggins, T.; Markar, S.R.; Arya, S.; Hanna, G.B.
Abstract Anastomotic leak is a potentially devastating complication following gastrointestinal anastomosis. Some surgeons believe that reinforcing the anastomosis with omentum reduces the incidence and severity of anastomotic leak. A comprehensive electronic search of EMBASE, Medline, Web of Science and Cochrane databases was performed. Pooled odds ratios (POR) were calculated for discrete variables. There were six studies investigating esophageal anastomosis and 3 studies investigating colorectal anastomosis identified by the literature search. A total of 2296 patients were included, 1073 with omentoplasty and 1223 without. In esophageal surgery omentoplasty significantly reduced the rate of anastomotic leak (2.9% vs 10.5% (POR = 0.28; 95% CI = 0.17 to 0.47; P < 0.0001), but there was no significant effect upon in-hospital mortality (2.3% vs. 2.5%; POR = 0.911 [95% CI 0.439–1.887]; P = 0.802) or anastomotic stricture between the two groups (6.6% vs 9.1%; POR = 0.842 [95% CI 0.331 to 2.145]; P = 0.720). In colorectal surgery there was no significant difference in anastomotic leak rate (5.0% vs 8.4%; POR: 0.50; 95% CI 0.21 to 1.17) or in-hospital mortality (4.2% vs 4.1%; POR: 0.90; 95% CI 0.34 to 2.41). The results of this analysis show that omentoplasty significantly reduced the rate of anastomotic leak following esophageal anastomosis but these results were not observed in colorectal anastomosis. Omentoplasty could be used as an adjunct technique to reduce the incidence of anastomotic leak in oesophageal anastomosis.